Spokane Parks (Images of America., 2023)
Parks are designed to give people a place to rest, to connect with nature, and to build community with others. Early developers feared Spokane could be just another boomtown and hoped a robust park system would encourage settlers to stay. The first park was deeded to the City of Spokane in 1891, and over the next 20 years, the city acquired nearly 2,000 acres for parkland. Among the elements that would come to define Spokane parks are amusement rides, a zoo, the Olmsted brothers, the Silver Spurs, and breathtaking natural beauty. It took the ingenuity of several people to create parks, parkways, and playfields that would eventually become the parks that many in Spokane use today. Revisit these places--remembering the sights, smells, and surroundings--through the moments and memories captured in archival records and photographs. From back cover.